RESOURCE ESTIMATE AND SIMULATION OF LATERITIC IRON ORE USING GEOSTATISTICAL APPLICATION METHOD THE ISLAND SEBUKU, SOUTH KALIMANTAN - WAHYU AJI (NIM : 22107014), GUNANDI
Mining Concessions (KP) of PT. Sebuku Lateritic Iron ores (SILO) is located in Sebuku Island, has total area of exploration + 9971 Ha. It administratively located in Kotabaru District, South Kalimantan Province. Methodology is used in this research collection of field data drilling and testpit results from PT. SILO. Assay data of laterite iron ore is divided into 3 (three) zones: Gravel Zone, Yellowish Zone and Greenish Zone. Research location is divided into 3 (three) blocks: Curing-1 Block, Curing-2 Block and Curing TP (testpit) Block. Variables for modelling are the accumulation grade of Fe, Ni and the thickness of each zone. In this study reseacrh Geostatistics methods used for resource estimation is Ordinary Kriging (OK) and Sequential Gaussian Simulation (SGS) method for simulatons. OK known as BLUE (Best Linear Unbiased Estimator), this method is linear because of the grade estimation was a linear combination of existing data and generate small error variance (Error Variance, R 2σ). While in SGS method, the multi-realization value of result estimation appropriate with initial data statistical distribution and local variability among the original data is taken into account. Resource classifications based on RKSD (Relative Kriging Standard Deviation) of the method OK value: measured resources for the estimate value <0.3, indicated resources with estimate value 0.3 to 0.5, and Inferred resources with estimation value> 0.5. Measured resources for Gravel zone in Curing-1 Block is about 2.26 million tons with average grade of 49.9% Fe; Curing-2 Block is about 2.78 million tons with average grade of 52.8% Fe; Curing -TP (testpit) Block is about 2.69 million tons with the average grade of 52.2% Fe. As a comparison, simulation with SGS method generate resources for Gravel zone about 2,85 million tons with average grade of 77% Fe in Curing-1 Block.